A method for preparing super antifouling light-sensitive glaze

Through ball mill mixing and spraying anti-fouling coatings, ultra-fouling light-sensitive glaze is prepared, which solves the problems of poor gloss, anti-fouling and wear resistance of existing light-sensitive glazes, and achieves higher gloss. Antifouling and wear resistance.

CN118851803BActive Publication Date: 2025-02-11ZIBO GOLD LION KING TECH CERAMICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411347065.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-11
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The existing light-sensitive gloss, anti-fouling properties and wear resistance of the light-sensitive gloss are poor, making it difficult to meet the market's dual pursuit of soft light-sensitive and highly anti-fouling properties.

Method used

A ball mill mixes feldspar, quartz, calcite and distilled water to prepare glaze slurry, and adds hardener, crosslinking agent, modified leveling agent and silane coupling agent to obtain pretreated glaze by spraying and firing, and then spraying and preventing Stain paint to form an ultra-foul-proof light-sensitive glaze.

Benefits of technology

It significantly improves the wear resistance, anti-fouling and gloss of the photosensitive glaze, forming a uniform and dense film, enhancing the cohesion and density of the glaze layer, reducing light scattering, and improving gloss and anti-fouling properties. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a super anti-fouling photosensitive glaze, and belongs to the technical field of photosensitive glaze preparation. The method for preparing the super anti-fouling photosensitive glaze comprises the following steps: step (1): adding feldspar, quartz, calcite and distilled water into a ball mill, mixing them evenly to obtain a glaze slurry, adding a hardener, a cross-linking agent, a modified leveling agent and a silane coupling agent into the glaze slurry in sequence, stirring and mixing them evenly to obtain a mixed glaze; step (2): applying the obtained mixed glaze evenly on a ceramic tile body by spraying, and then drying, adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze; step (3): spraying the prepared anti-fouling coating evenly on the surface of the pre-treated glaze, drying, and obtaining a super anti-fouling photosensitive glaze. The photosensitive glaze prepared by the method has excellent gloss, pollution resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photosensitive glaze preparation, and in particular relates to a method for preparing a super anti-fouling photosensitive glaze. Background Art

[0002] In the field of contemporary home decoration, ceramic tiles have always occupied an important market position due to their durability, beauty and easy cleaning. However, with the improvement of consumers' aesthetic level and the improvement of quality of life, traditional ceramic glazes can no longer meet the market's dual pursuit of soft light and high anti-fouling performance. As consumers' requirements for the quality of home environment increase, they not only pay attention to the aesthetics of ceramic tiles, but also pay more attention to their practical performance, such as anti-fouling and wear resistance. Especially in areas prone to stains such as kitchens and bathrooms, a ceramic tile that can maintain an elegant light perception and easily resist stains has won wide favor in the market.

[0003] Patent CN112456967A discloses a kind of stain-resistant glazed tile and its production process. The stain-resistant glazed tile comprises a whole brick body and an anti-fouling glaze layer sprayed on the surface of the whole brick body. The whole brick body comprises the following components by percentage: potassium feldspar 10%-15%, sodium feldspar 10%-20%, spodumene 5%-15%, calcined kaolin 5%-15%, burnt talc 1%-3%, and black mud 30%-55%; the anti-fouling glaze layer comprises the following components by percentage: potassium feldspar 10%-20%, sodium feldspar 20%-25%, calcite 18%-22%, kaolin 8%-13%, burnt talc 3%-7%, quartz powder 5%-10%, zinc oxide 2%-6%, calcined kaolin 8%-12%, and barium carbonate 2%-6%. The stain-resistant glazed tile can be prepared by the invention, but its glossiness, stain resistance and wear resistance still have room for improvement. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a super antifouling photosensitive glaze, so as to solve the technical problems of poor gloss, antifouling property and wear resistance of the photosensitive glaze in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a super antifouling light-sensitive glaze, comprising the following steps:

[0007] Step (1): adding feldspar, quartz, calcite and distilled water into a ball mill, mixing them evenly to obtain a glaze slurry, adding a hardener, a cross-linking agent, a modified leveling agent and a silane coupling agent into the glaze slurry in sequence, stirring and mixing them evenly to obtain a mixed glaze;

[0008] Step (2): applying the obtained mixed glaze evenly on the ceramic tile body by spraying, and then drying, and adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze;

[0009] Step (3): spraying the prepared antifouling coating evenly on the surface of the pretreated glaze, and drying it to obtain a super antifouling light-sensitive glaze.

[0010] Preferably, in step (1), the dosage ratio of feldspar, quartz, calcite and distilled water is (12-18) kg: (4-9) kg: (1-3) kg: (5-10) L. During the ball milling mixing process, the ball milling speed is 200-300 rpm, the ball milling time is 8-12 h, the mass ratio of glaze slurry, hardener, cross-linking agent, modified leveling agent and silane coupling agent is (5-9): (0.12-0.18): (0.08-0.15): (0.05-0.19): (0.13-0.17), and the stirring mixing time is 4-8 h.

[0011] Preferably, the method for preparing the modified leveling agent comprises the following steps:

[0012] Q1: maleic anhydride is added to a container containing acetone, and p-aminophenol is added under ice bath conditions. After low-temperature reaction, the filtrate is removed by suction, and the solid filter is vacuum dried to obtain compound 1, which is then added to a container containing p-toluenesulfonic acid, followed by a mixed solution of toluene and N,N-dimethylformamide, and heated to reflux for reaction. After the reaction is completed, the mixture is cooled, and deionized water is added to obtain a precipitate. The filtrate is removed by suction, and the solid filter is vacuum dried, dissolved, and recrystallized to obtain compound 2;

[0013] Q2: Aniline and paraformaldehyde are dissolved in a mixed solution of N,N-dimethylacetamide and xylene, stirred, and compound 2 is added, refluxed, and after the reaction is completed, cooled, deionized water is added, filtered, washed, and vacuum dried to obtain compound 3;

[0014] Q3: Compound 3, 4-cyano-4-(thiobenzoyl)valeric acid, poly(ethylene glycol) methacrylate and azobisisobutyronitrile were dissolved in 1,4-dioxane, anisole was added to obtain a mixed solution, the mixed solution was added to a reaction vessel, deoxygenated, and polymerized in an oil bath. After the polymerization reaction was completed, the solution was precipitated and vacuum dried to obtain a modified leveling agent.

[0015] In the above process, the synthetic reaction formula of the modified leveling agent is as follows:

[0016]

[0017] Preferably, in Q1, the molar ratio of maleic anhydride to p-aminophenol is (1-2): (0.9-1.9), the low temperature reaction temperature is 0-1°C, the low temperature reaction time is 3-5h, the vacuum drying temperature is 60-80°C, the vacuum drying time is 10-12h, and the amount ratio of compound 1, p-toluenesulfonic acid, toluene and N,N-dimethylformamide is (8.6-11.2) g: (0.9-1.2) g: (50-65 )mL:(10-13)mL, the heating reflux reaction temperature is 110-120℃, and the reaction time is 8-10h; in Q2, the molar ratio of aniline, polyformaldehyde and compound 2 is (1-2):(2-4.2):(1-1.9), the stirring time is 30-45min, the reflux reaction temperature is 120-130℃, the reaction time is 6-8h, and it is washed with 5wt% sodium bicarbonate solution and then washed with deionized water.

[0018] Preferably, in Q3, the molar ratio of compound 3, 4-cyano-4-(thiobenzoyl)valeric acid, poly(ethylene glycol) methacrylate and azobisisobutyronitrile is (2-3):(0.1-0.15):(8-12):(0.02-0.03), the oil bath polymerization temperature is 70-90°C, the polymerization time is 14-16h, and the vacuum drying time is 20-24h.

[0019] Preferably, the method for preparing the antifouling coating comprises the following steps:

[0020] S1: adding silica to a mixed solution of ethanol and water, ultrasonically treating to obtain a dispersion, heating and stirring, dropping ammonia water and (3-aminopropyl)triethoxysilane, condensing and refluxing, centrifuging, washing the product, and obtaining modified silica;

[0021] S2: adding modified silica to N,N-dimethylformamide, ultrasonically treating to obtain a modified silica solution, then adding styrene-maleic anhydride copolymer to N,N-dimethylformamide to obtain a copolymer solution, slowly dropping the modified silica solution into the copolymer solution, controlling the dropping temperature, and after the dropping is completed, condensing and refluxing, centrifuging, washing, and drying to obtain a copolymer composite silica;

[0022] S3: Add the copolymer composite silica and isophorone diisocyanate to tetrahydrofuran, heat to react, and obtain a prepolymer; then add 4,4'-dihydroxydiphenyl disulfide to the prepolymer, continue to heat to react, and after the reaction is completed, add diacetyl oxime, heat to react, and after the reaction is completed, cool to obtain an antifouling coating.

[0023] In the above process, styrene-maleic anhydride copolymer is first grafted onto the surface of silica to prepare a copolymer composite silica with amphiphilic properties, and then an antifouling coating is prepared with the copolymer composite silica and isophorone diisocyanate as the main chain, and 4,4'-dihydroxydiphenyl disulfide and dimethylglyoxime as chain extenders.

[0024] Preferably, in S1, the amount ratio of silicon dioxide, ethanol, water, ammonia water and (3-aminopropyl)triethoxysilane is (2-4) g: (175-350) mL: (25-50) mL: (5-10) mL: (1-2) mL, the ultrasonic treatment time is 10-20 min, the heating temperature is 70-80°C, the rotation speed is 500-700 rpm, the stirring time is 30-45 min, the condensation reflux time is 8-10 h, and the product is washed with ethanol 3-5 times.

[0025] Preferably, in S2, the mass ratio of modified silica and styrene-maleic anhydride copolymer is (2-4): (1-2), the dropping temperature is 80-90°C, the condensation reflux time is 10-12h, first washed with N,N-dimethylformamide, then washed with ethanol, the drying temperature is 60-80°C, and the time is 10-12h.

[0026] Preferably, in S3, the molar ratio of the copolymer composite silica, isophorone diisocyanate, 4,4'-dihydroxydiphenyl disulfide and dimethylglyoxime is (4-8): (5.2-10): (0.6-1.1): (0.6-1.2), the heating reaction temperature is 40-50°C, the time is 3-5h, the heating reaction temperature is continued to be 40-50°C, the time is 3-4h, and the heating reaction temperature is 60-70°C, and the time is 2-3h.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. The present invention firstly uses maleic anhydride, p-aminophenol, aniline, polyformaldehyde, 4-cyano-4-(thiobenzoyl)valeric acid and poly(ethylene glycol) methacrylate as raw materials to prepare a modified leveling agent, and then uses silicon dioxide, styrene-maleic anhydride copolymer, isophorone diisocyanate, 4,4'-dihydroxydiphenyl disulfide and dimethylglyoxime as raw materials to prepare an antifouling coating. The modified leveling agent and the antifouling coating are added into the preparation process of the super antifouling photosensitive glaze, which can effectively improve the wear resistance, antifouling property and glossiness of the photosensitive glaze.

[0029] 2. The present invention uses a reversible addition-fragmentation chain transfer polymerization method, uses 4-cyano-4-(thiobenzoyl) valeric acid as a chain transfer agent, and uses the prepared compound 3 and poly(ethylene glycol) methacrylate as polymerization monomers. Under the initiation of azobisisobutyronitrile, a modified leveling agent is obtained. The polymer component in the modified leveling agent has good fluidity and spreadability. In the film-forming process of the light-sensitive glaze, the polymer can quickly migrate to the surface of the glaze layer to form a uniform and dense film. The presence of the film can fill the tiny bumps on the surface of the glaze layer, making the surface more It makes the surface smoother, thereby reducing scattering when reflecting light, increasing specular reflection and improving glossiness. The modified leveling agent can also reduce the surface tension of the glaze layer, so that the glaze layer can be better leveled during the drying and curing process, reducing defects such as shrinkage holes and pinholes caused by uneven surface tension. The reduction of defects helps to improve the smoothness and glossiness of the glaze layer. At the same time, lower surface tension is conducive to improving anti-fouling performance. Stronger intermolecular bonding force helps to improve the cohesion and density of the glaze layer, reduce light scattering caused by intermolecular gaps, and improve glossiness.

[0030] 3. The present invention uses silicon dioxide, styrene-maleic anhydride copolymer, isophorone diisocyanate, 4,4'-dihydroxydiphenyl disulfide and dimethylglyoxime as raw materials to prepare an antifouling coating, which is sprayed onto the surface of the pretreated glaze as a coating, which can effectively improve the antifouling and wear resistance of the glaze. The silicon dioxide in the antifouling coating has excellent hydrophobicity after treatment, which helps to reduce the adhesion of stains on the surface of the photosensitive glaze. The formed polyurethane / polyurea cross-linked structure can make the coating more compact, effectively block the penetration of stains, and improve the pollution resistance; the formed cross-linked structure significantly increases the hardness of the coating, so that it can better resist wear when subjected to external friction, and extend the service life of the coating. At the same time, the cross-linked structure formed by the combination of modified silicon dioxide and styrene-maleic anhydride copolymer forms good adhesion between the coating and the photosensitive glaze substrate, ensuring that the coating is not easy to fall off when subjected to external force, thereby improving the wear resistance of the coating. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1: This example discloses a method for preparing a modified leveling agent, comprising the following steps:

[0033] Q1: 1.5 g of maleic anhydride was added to a container containing 50 mL of acetone, and 1.56 g of p-aminophenol was added under ice bath conditions. After reacting at 0°C for 3 h, the filtrate was removed by suction, and the solid was vacuum dried at 80°C for 10 h to obtain compound 1. Subsequently, 9.9 g of compound 1 was added to a container containing 1.05 g of p-toluenesulfonic acid, and then a mixed solution of 57.5 mL of toluene and 11.5 mL of N,N-dimethylformamide was added, and the mixture was heated to reflux at 110°C for 10 h. After the reaction was completed, the mixture was cooled, deionized water was added, and a precipitate was obtained. The filtrate was removed by suction, and the solid was vacuum dried, dissolved, and recrystallized to obtain compound 2;

[0034] Q2: 2.79 g of aniline and 1.86 g of paraformaldehyde were dissolved in a mixed solution of 15 mL of N, N-dimethylacetamide and 15 mL of xylene, stirred for 30 min, and then 5.48 g of compound 2 was added. The mixture was refluxed at 120 °C for 8 h. After the reaction was completed, the mixture was cooled, deionized water was added, filtered, washed with 5 wt% sodium bicarbonate solution, and then washed with deionized water, and dried in vacuo to obtain compound 3.

[0035] Q3: 0.77 g of compound 3, 34.88 mg of 4-cyano-4-(thiobenzoyl)valeric acid, 3 g of poly(ethylene glycol) methacrylate and 4.04 mg of azobisisobutyronitrile were dissolved in 10 mL of 1,4-dioxane, and 0.02 g of anisole was added to obtain a mixed solution. The mixed solution was added to a reaction vessel, deoxygenated, and polymerized in an oil bath at 80°C for 16 h. After the polymerization reaction was completed, the solution was precipitated and vacuum dried for 24 h to obtain a modified leveling agent.

[0036] This embodiment discloses a method for preparing an antifouling coating, comprising the following steps:

[0037] S1: 3 g of silica was added to a mixed solution of 263 mL of ethanol and 38 mL of water, and the dispersion was obtained by ultrasonic treatment for 20 min. After stirring at 700 rpm and 80 °C for 45 min, 7.5 mL of ammonia water and 1.5 mL of (3-aminopropyl) triethoxysilane were added dropwise, and the mixture was condensed and refluxed for 10 h. The mixture was centrifuged and the product was washed with ethanol for 3 times to obtain modified silica.

[0038] S2: 3 g of modified silica was added to 150 mL of N, N-dimethylformamide, and ultrasonic treatment was performed for 10 min to obtain a modified silica solution. Then, 1.5 g of styrene-maleic anhydride copolymer was added to 50 mL of N, N-dimethylformamide to obtain a copolymer solution. The modified silica solution was slowly added dropwise to the copolymer solution, and the dropping temperature was controlled to be 80°C. After the dropwise addition was completed, the solution was condensed and refluxed for 12 h, centrifuged, first washed with N, N-dimethylformamide, then washed with ethanol, and dried at 80°C for 12 h to obtain a copolymer composite silica.

[0039] S3: Add 10.4g of copolymer composite silica and 1.46g of isophorone diisocyanate to 10mL of tetrahydrofuran, heat to 40°C for reaction for 5h to obtain a prepolymer, then add 0.16g of 4,4'-dihydroxydiphenyl disulfide to the prepolymer, continue to heat to 40°C for reaction for 4h. After the reaction is completed, add 0.09g of dimethylglyoxime, heat to 65°C for reaction for 3h. After the reaction is completed, cool to obtain an antifouling coating.

[0040] This embodiment discloses a method for preparing a super antifouling light-sensitive glaze, comprising the following steps:

[0041] Step (1): 15 kg of feldspar, 6.5 kg of quartz, 2 kg of calcite and 7.5 L of distilled water were added to a ball mill, and the mixture was mixed at 300 rpm for 12 h to obtain a glaze slurry. 0.15 kg of a hardener, 0.11 kg of a cross-linking agent, 0.12 kg of a modified leveling agent and 0.15 kg of a silane coupling agent were added to 7 kg of the glaze slurry in sequence, and the mixture was stirred for 8 h to obtain a mixed glaze.

[0042] Step (2): applying the obtained mixed glaze evenly on the ceramic tile body by spraying, and then drying, and adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze;

[0043] Step (3): spraying the prepared antifouling coating evenly on the surface of the pretreated glaze, and drying it to obtain a super antifouling light-sensitive glaze.

[0044] Example 2: This example discloses a method for preparing a modified leveling agent, comprising the following steps:

[0045] Q1: 1 g of maleic anhydride was added to a container containing 50 mL of acetone, and 1 g of p-aminophenol was added under ice bath conditions. After reacting at 0°C for 3 h, the filtrate was removed by suction, and the solid was vacuum dried at 80°C for 10 h to obtain compound 1. Subsequently, 8.6 g of compound 1 was added to a container containing 0.9 g of p-toluenesulfonic acid, and then a mixed solution of 50 mL of toluene and 10 mL of N,N-dimethylformamide was added, and the mixture was heated to reflux at 110°C for 10 h. After the reaction was completed, the mixture was cooled, and deionized water was added to obtain a precipitate. The filtrate was removed by suction, and the solid was vacuum dried, dissolved, and recrystallized to obtain compound 2;

[0046] Q2: 1.86 g of aniline and 1.2 g of paraformaldehyde were dissolved in a mixed solution of 15 mL of N,N-dimethylacetamide and 15 mL of xylene, stirred for 30 min, and then 3.78 g of compound 2 was added. The mixture was refluxed at 120 °C for 8 h. After the reaction was completed, the mixture was cooled, deionized water was added, filtered, washed with 5 wt% sodium bicarbonate solution, and then washed with deionized water, and dried in vacuo to obtain compound 3.

[0047] Q3: 0.61 g of compound 3, 27.9 mg of 4-cyano-4-(thiobenzoyl)valeric acid, 2.4 g of poly(ethylene glycol) methacrylate and 3.28 mg of azobisisobutyronitrile were dissolved in 10 mL of 1,4-dioxane, and 0.02 g of anisole was added to obtain a mixed solution. The mixed solution was added to a reaction vessel, deoxygenated, and polymerized in an oil bath at 80°C for 16 h. After the polymerization reaction was completed, the solution was precipitated and vacuum dried for 24 h to obtain a modified leveling agent.

[0048] This embodiment discloses a method for preparing an antifouling coating, comprising the following steps:

[0049] S1: 2 g of silica was added to a mixed solution of 175 mL of ethanol and 25 mL of water, and ultrasonic treatment was performed for 20 min to obtain a dispersion. After stirring at 700 rpm and 80 °C for 45 min, 5 mL of ammonia water and 1 mL of (3-aminopropyl)triethoxysilane were added dropwise, condensed and refluxed for 10 h, centrifuged, and the product was washed with ethanol 3 times to obtain modified silica;

[0050] S2: 2 g of modified silica was added to 150 mL of N, N-dimethylformamide, and ultrasonic treatment was performed for 10 min to obtain a modified silica solution. Then, 1 g of styrene-maleic anhydride copolymer was added to 50 mL of N, N-dimethylformamide to obtain a copolymer solution. The modified silica solution was slowly added dropwise to the copolymer solution, and the dropping temperature was controlled to be 80°C. After the dropwise addition was completed, the solution was condensed and refluxed for 12 h, and centrifuged. The solution was first washed with N, N-dimethylformamide, and then washed with ethanol, and dried at 80°C for 12 h to obtain a copolymer composite silica.

[0051] S3: Add 6.93g of copolymer composite silica and 1g of isophorone diisocyanate to 10mL of tetrahydrofuran, heat to react at 40°C for 5h to obtain a prepolymer, then add 0.11g of 4,4'-dihydroxydiphenyl disulfide to the prepolymer, continue to heat to react at 40°C for 4h, after the reaction is completed, add 0.06g of dimethylglyoxime, heat to react at 65°C for 3h, after the reaction is completed, cool to obtain an antifouling coating.

[0052] This embodiment discloses a method for preparing a super antifouling light-sensitive glaze, comprising the following steps:

[0053] Step (1): adding 12 kg of feldspar, 4 kg of quartz, 1 kg of calcite and 5 L of distilled water into a ball mill, and mixing them by ball milling at 300 rpm for 12 h. Mixing them evenly to obtain a glaze slurry. Adding 0.12 kg of a hardener, 0.08 kg of a cross-linking agent, 0.05 kg of a modified leveling agent and 0.13 kg of a silane coupling agent into 5 kg of the glaze slurry in sequence, and stirring and mixing for 8 h to obtain a mixed glaze.

[0054] Step (2): applying the obtained mixed glaze evenly on the ceramic tile body by spraying, and then drying, and adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze;

[0055] Step (3): spraying the prepared antifouling coating evenly on the surface of the pretreated glaze, and drying it to obtain a super antifouling light-sensitive glaze.

[0056] Example 3: This example discloses a method for preparing a modified leveling agent, comprising the following steps:

[0057] Q1: 2 g of maleic anhydride was added to a container containing 50 mL of acetone, and 2.11 g of p-aminophenol was added under ice bath conditions. After reacting at 0°C for 3 h, the filtrate was removed by suction, and the solid was vacuum dried at 80°C for 10 h to obtain compound 1. Subsequently, 11.2 g of compound 1 was added to a container containing 1.2 g of p-toluenesulfonic acid, and then a mixed solution of 65 mL of toluene and 13 mL of N,N-dimethylformamide was added, and the mixture was heated to reflux at 110°C for 10 h. After the reaction was completed, the mixture was cooled, deionized water was added, and a precipitate was obtained. The filtrate was removed by suction, and the solid was vacuum dried, dissolved, and recrystallized to obtain compound 2;

[0058] Q2: 3.72 g of aniline and 2.52 g of paraformaldehyde were dissolved in a mixed solution of 15 mL of N, N-dimethylacetamide and 15 mL of xylene, stirred for 30 min, and then 7.18 g of compound 2 was added. The mixture was refluxed at 120 °C for 8 h. After the reaction was completed, the mixture was cooled, deionized water was added, filtered, washed with 5 wt% sodium bicarbonate solution, and then washed with deionized water, and dried in vacuo to obtain compound 3.

[0059] Q3: 0.92 g of compound 3, 41.85 mg of 4-cyano-4-(thiobenzoyl)valeric acid, 3.6 g of poly(ethylene glycol) methacrylate and 4.8 mg of azobisisobutyronitrile were dissolved in 10 mL of 1,4-dioxane, and 0.02 g of anisole was added to obtain a mixed solution. The mixed solution was added to a reaction vessel, deoxygenated, and polymerized in an oil bath at 80°C for 16 h. After the polymerization reaction was completed, the solution was precipitated and vacuum dried for 24 h to obtain a modified leveling agent.

[0060] This embodiment discloses a method for preparing an antifouling coating, comprising the following steps:

[0061] S1: 4 g of silica was added to a mixed solution of 350 mL of ethanol and 50 mL of water, and the solution was ultrasonically treated for 20 min to obtain a dispersion. After stirring at 700 rpm and 80 °C for 45 min, 10 mL of ammonia water and 2 mL of (3-aminopropyl)triethoxysilane were added dropwise, and the mixture was condensed and refluxed for 10 h. The mixture was centrifuged and the product was washed with ethanol for 3 times to obtain modified silica.

[0062] S2: 4 g of modified silica was added to 150 mL of N, N-dimethylformamide, and ultrasonic treatment was performed for 10 min to obtain a modified silica solution. Then, 2 g of styrene-maleic anhydride copolymer was added to 50 mL of N, N-dimethylformamide to obtain a copolymer solution. The modified silica solution was slowly added dropwise to the copolymer solution, and the dropping temperature was controlled to be 80°C. After the dropwise addition was completed, the solution was condensed and refluxed for 12 h, and centrifuged. The solution was first washed with N, N-dimethylformamide, and then washed with ethanol, and dried at 80°C for 12 h to obtain a copolymer composite silica.

[0063] S3: Add 13.86g of copolymer composite silica and 1.92g of isophorone diisocyanate to 10mL of tetrahydrofuran, heat to 40°C for reaction for 5h to obtain a prepolymer, then add 0.21g of 4,4'-dihydroxydiphenyl disulfide to the prepolymer, continue to heat to 40°C for reaction for 4h. After the reaction is completed, add 0.12g of dimethylglyoxime, heat to 65°C for reaction for 3h. After the reaction is completed, cool to obtain an antifouling coating.

[0064] This embodiment discloses a method for preparing a super antifouling light-sensitive glaze, comprising the following steps:

[0065] Step (1): 18 kg of feldspar, 9 kg of quartz, 3 kg of calcite and 10 L of distilled water were added to a ball mill, and the mixture was mixed at 300 rpm for 12 h to obtain a glaze slurry. 0.18 kg of a hardener, 0.15 kg of a cross-linking agent, 0.19 kg of a modified leveling agent and 0.17 kg of a silane coupling agent were added to the 9 kg glaze slurry in sequence, and the mixture was stirred for 8 h to obtain a mixed glaze.

[0066] Step (2): applying the obtained mixed glaze evenly on the ceramic tile body by spraying, and then drying, and adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze;

[0067] Step (3): spraying the prepared antifouling coating evenly on the surface of the pretreated glaze, and drying it to obtain a super antifouling light-sensitive glaze.

[0068] Embodiment 4: This embodiment discloses a method for preparing a modified leveling agent, comprising the following steps:

[0069] Q1: 1.2 g of maleic anhydride was added to a container containing 50 mL of acetone, and 1.28 g of p-aminophenol was added under ice bath conditions. After reacting at 0°C for 3 h, the filtrate was removed by suction, and the solid was vacuum dried at 80°C for 10 h to obtain compound 1. Subsequently, 9.25 g of compound 1 was added to a container containing 0.98 g of p-toluenesulfonic acid, and then a mixed solution of 52 mL of toluene and 11 mL of N,N-dimethylformamide was added, and the mixture was heated to reflux at 110°C for 10 h. After the reaction was completed, the mixture was cooled, deionized water was added, and a precipitate was obtained. The filtrate was removed by suction, and the solid was vacuum dried, dissolved, and recrystallized to obtain compound 2;

[0070] Q2: 2.33 g of aniline and 1.53 g of paraformaldehyde were dissolved in a mixed solution of 15 mL of N, N-dimethylacetamide and 15 mL of xylene, stirred for 30 min, and then 4.63 g of compound 2 was added. The mixture was refluxed at 120 °C for 8 h. After the reaction was completed, the mixture was cooled, deionized water was added, filtered, washed with 5 wt% sodium bicarbonate solution, and then washed with deionized water, and dried in vacuo to obtain compound 3.

[0071] Q3: 0.69 g of compound 3, 31.4 mg of 4-cyano-4-(thiobenzoyl)valeric acid, 2.8 g of poly(ethylene glycol) methacrylate and 3.66 mg of azobisisobutyronitrile were dissolved in 10 mL of 1,4-dioxane, and 0.02 g of anisole was added to obtain a mixed solution. The mixed solution was added to a reaction vessel, deoxygenated, and polymerized in an oil bath at 80°C for 16 h. After the polymerization reaction was completed, the solution was precipitated and vacuum dried for 24 h to obtain a modified leveling agent.

[0072] This embodiment discloses a method for preparing an antifouling coating, comprising the following steps:

[0073] S1: 2.5 g of silica was added to a mixed solution of 219 mL of ethanol and 32 mL of water, and the solution was ultrasonically treated for 20 min to obtain a dispersion. After stirring at 700 rpm and 80 °C for 45 min, 6 mL of ammonia water and 1.2 mL of (3-aminopropyl)triethoxysilane were added dropwise, and the mixture was condensed and refluxed for 10 h. The mixture was centrifuged and the product was washed with ethanol for 3 times to obtain modified silica.

[0074] S2: Add 2.5 g of modified silica to 150 mL of N,N-dimethylformamide, and perform ultrasonic treatment for 10 min to obtain a modified silica solution. Then, add 1.2 g of styrene-maleic anhydride copolymer to 50 mL of N,N-dimethylformamide to obtain a copolymer solution. Slowly drop the modified silica solution into the copolymer solution, and control the dropping temperature to be 80°C. After the dropwise addition is completed, condense and reflux for 12 h, centrifuge, first wash with N,N-dimethylformamide, then wash with ethanol, and dry at 80°C for 12 h to obtain a copolymer composite silica.

[0075] S3: Add 8.67g of copolymer composite silica and 1.23g of isophorone diisocyanate to 10mL of tetrahydrofuran, heat to 40°C for reaction for 5h to obtain a prepolymer, then add 0.14g of 4,4'-dihydroxydiphenyl disulfide to the prepolymer, continue to heat to 40°C for reaction for 4h, after the reaction is completed, add 0.07g of dimethylglyoxime, heat to 65°C for reaction for 3h, after the reaction is completed, cool to obtain an antifouling coating.

[0076] This embodiment discloses a method for preparing a super antifouling light-sensitive glaze, comprising the following steps:

[0077] Step (1): 14 kg of feldspar, 5 kg of quartz, 1.5 kg of calcite and 8 L of distilled water were added to a ball mill, and the mixture was mixed at 300 rpm for 12 h to obtain a glaze slurry. 0.13 kg of a hardener, 0.09 kg of a cross-linking agent, 0.14 kg of a modified leveling agent and 0.14 kg of a silane coupling agent were added to 6 kg of the glaze slurry in sequence, and the mixture was stirred for 8 h to obtain a mixed glaze.

[0078] Step (2): applying the obtained mixed glaze evenly on the ceramic tile body by spraying, and then drying, and adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze;

[0079] Step (3): spraying the prepared antifouling coating evenly on the surface of the pretreated glaze, and drying it to obtain a super antifouling light-sensitive glaze.

[0080] Example 5: This example discloses a method for preparing a modified leveling agent, comprising the following steps:

[0081] Q1: 1.7 g of maleic anhydride was added to a container containing 50 mL of acetone, and 1.84 g of p-aminophenol was added under ice bath conditions. After reacting at 0°C for 3 h, the filtrate was removed by suction, and the solid was vacuum dried at 80°C for 10 h to obtain compound 1. Subsequently, 10.6 g of compound 1 was added to a container containing 1.13 g of p-toluenesulfonic acid, and then a mixed solution of 61 mL of toluene and 12 mL of N,N-dimethylformamide was added, and the mixture was heated to reflux at 110°C for 10 h. After the reaction was completed, the mixture was cooled, deionized water was added, and a precipitate was obtained. The filtrate was removed by suction, and the solid was vacuum dried, dissolved, and recrystallized to obtain compound 2;

[0082] Q2: 3.26 g of aniline and 2.19 g of paraformaldehyde were dissolved in a mixed solution of 15 mL of N, N-dimethylacetamide and 15 mL of xylene, stirred for 30 min, and then 6.33 g of compound 2 was added. The mixture was refluxed at 120 °C for 8 h. After the reaction was completed, the mixture was cooled, deionized water was added, filtered, washed with 5 wt% sodium bicarbonate solution, and then washed with deionized water, and dried in vacuo to obtain compound 3.

[0083] Q3: 0.85 g of compound 3, 38.37 mg of 4-cyano-4-(thiobenzoyl)valeric acid, 3.2 g of poly(ethylene glycol) methacrylate and 4.42 mg of azobisisobutyronitrile were dissolved in 10 mL of 1,4-dioxane, and 0.02 g of anisole was added to obtain a mixed solution. The mixed solution was added to a reaction vessel, deoxygenated, and polymerized in an oil bath at 80°C for 16 h. After the polymerization reaction was completed, the solution was precipitated and vacuum dried for 24 h to obtain a modified leveling agent.

[0084] This embodiment discloses a method for preparing an antifouling coating, comprising the following steps:

[0085] S1: 3.5 g of silica was added to a mixed solution of 307 mL of ethanol and 45 mL of water, and the solution was ultrasonically treated for 20 min to obtain a dispersion. After stirring at 700 rpm and 80 °C for 45 min, 9 mL of ammonia water and 1.7 mL of (3-aminopropyl)triethoxysilane were added dropwise, and the mixture was condensed and refluxed for 10 h. The mixture was centrifuged and the product was washed with ethanol for 3 times to obtain modified silica.

[0086] S2: 3.5 g of modified silica was added to 150 mL of N, N-dimethylformamide, and ultrasonic treatment was performed for 10 min to obtain a modified silica solution. Then, 1.7 g of styrene-maleic anhydride copolymer was added to 50 mL of N, N-dimethylformamide to obtain a copolymer solution. The modified silica solution was slowly added dropwise to the copolymer solution, and the dropping temperature was controlled to be 80°C. After the dropwise addition was completed, the solution was condensed and refluxed for 12 h, and centrifuged. The solution was first washed with N, N-dimethylformamide, and then washed with ethanol, and dried at 80°C for 12 h to obtain a copolymer composite silica.

[0087] S3: Add 12.13g of copolymer composite silica and 1.69g of isophorone diisocyanate to 10mL of tetrahydrofuran, heat to 40°C for reaction for 5h to obtain a prepolymer, then add 0.18g of 4,4'-dihydroxydiphenyl disulfide to the prepolymer, continue to heat to 40°C for reaction for 4h. After the reaction is completed, add 0.1g of dimethylglyoxime, heat to 65°C for reaction for 3h. After the reaction is completed, cool to obtain an antifouling coating.

[0088] This embodiment discloses a method for preparing a super antifouling light-sensitive glaze, comprising the following steps:

[0089] Step (1): 16 kg of feldspar, 8 kg of quartz, 2.5 kg of calcite and 6 L of distilled water are added to a ball mill, and the mixture is ball-milled at 300 rpm for 12 h to obtain a glaze slurry. 0.16 kg of a hardener, 0.12 kg of a cross-linking agent, 0.17 kg of a modified leveling agent and 0.16 kg of a silane coupling agent are sequentially added to the 8 kg glaze slurry, and the mixture is stirred and mixed for 8 h to obtain a mixed glaze.

[0090] Step (2): applying the obtained mixed glaze evenly on the ceramic tile body by spraying, and then drying, and adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze;

[0091] Step (3): spraying the prepared antifouling coating evenly on the surface of the pretreated glaze, and drying it to obtain a super antifouling light-sensitive glaze.

[0092] Comparative Example 1: Compared with Example 1, in the preparation process of the modified leveling agent in Comparative Example 1, poly(ethylene glycol) methacrylate is not added, and other conditions remain unchanged.

[0093] Comparative Example 2: Compared with Example 1, in the preparation process of the antifouling coating in Comparative Example 2, no styrene-maleic anhydride copolymer is added, and other conditions remain unchanged.

[0094] Comparative Example 3: Compared with Example 1, in the preparation process of the antifouling coating in Comparative Example 3, isophorone diisocyanate is not added, and other conditions remain unchanged.

[0095] Comparative Example 4: Compared with Example 1, in the preparation process of the super anti-fouling photosensitive glaze in Comparative Example 4, no modified leveling agent is added, and other conditions remain unchanged.

[0096] Comparative Example 5: Compared with Example 1, in the preparation process of the super antifouling photosensitive glaze in Comparative Example 5, no antifouling coating is added, and other conditions remain unchanged.

[0097] The samples prepared according to Examples 1-5 and Comparative Examples 1-5 were tested, the wear resistance of the samples was tested according to GB / T 3810.7-2016, the anti-pollution performance of the samples was tested according to GB / T 3810.14-2016, and the glossiness of the samples was tested according to GB / T 3295-1996. The test results are shown in Table 1:

[0098] Table 1

[0099] project Wear resistance Anti-pollution performance Glossiness Example 1 Level 5 Level 5 98 Example 2 Level 5 Level 5 95 Example 3 Level 5 Level 5 96 Example 4 Level 5 Level 5 93 Example 5 Level 5 Level 5 94 Comparative Example 1 Level 5 Level 4 78 Comparative Example 2 Level 4 Level 4 92 Comparative Example 3 Level 4 Level 4 91 Comparative Example 4 Level 5 Level 3 72 Comparative Example 5 Level 3 Level 3 90

[0100] It can be seen from the test results in Table 1 that the super antifouling photosensitive glaze prepared in Examples 1-5 of the present invention has excellent wear resistance, antifouling performance and glossiness. By comparing Comparative Example 1 with Examples 1-5, it can be seen that the addition of poly (ethylene glycol) methacrylate can make the obtained super antifouling photosensitive glaze have excellent antifouling performance and glossiness; by comparing Comparative Example 2 with Examples 1-5, it can be seen that the addition of styrene-maleic anhydride copolymer can make the obtained super antifouling photosensitive glaze have excellent wear resistance and antifouling performance; by comparing Comparative Example 3 with Examples 1-5, it can be seen that the addition of isophorone diisocyanate can make the obtained super antifouling photosensitive glaze have excellent wear resistance and antifouling performance; by comparing Comparative Example 4 with Examples 1-5, it can be seen that the addition of a modified leveling agent can make the obtained super antifouling photosensitive glaze have excellent antifouling performance and glossiness; by comparing Comparative Example 5 with Examples 1-5, it can be seen that the addition of an antifouling coating can make the obtained super antifouling photosensitive glaze have excellent wear resistance and antifouling performance.

[0101] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0102] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a super antifouling light-sensitive glaze, characterized in that: The following steps are involved: Step (1): adding feldspar, quartz, calcite and distilled water into a ball mill, mixing them evenly to obtain a glaze slurry, adding a hardener, a cross-linking agent, a modified leveling agent and a silane coupling agent into the glaze slurry in sequence, stirring and mixing them evenly to obtain a mixed glaze; Step (2): applying the obtained mixed glaze evenly on the ceramic tile body by spraying, and then drying, and adding the dried ceramic tile body into a kiln for firing to obtain a pre-treated glaze; Step (3): spraying the prepared antifouling coating evenly on the surface of the pretreated glaze, and drying to obtain a super antifouling light-sensitive glaze; The preparation method of the modified leveling agent comprises the following steps: Q1: maleic anhydride is added to a container containing acetone, and p-aminophenol is added under ice bath conditions. After low-temperature reaction, the filtrate is removed by suction, and the solid filter is vacuum dried to obtain compound 1, which is then added to a container containing p-toluenesulfonic acid, followed by a mixed solution of toluene and N,N-dimethylformamide, and heated to reflux for reaction. After the reaction is completed, the mixture is cooled, and deionized water is added to obtain a precipitate. The filtrate is removed by suction, and the solid filter is vacuum dried, dissolved, and recrystallized to obtain compound 2; Q2: Aniline and paraformaldehyde are dissolved in a mixed solution of N,N-dimethylacetamide and xylene, stirred, and compound 2 is added, refluxed, and after the reaction is completed, cooled, deionized water is added, filtered, washed, and vacuum dried to obtain compound 3; Q3: Compound 3, 4-cyano-4-(thiobenzoyl)valeric acid, poly(ethylene glycol) methacrylate and azobisisobutyronitrile were dissolved in 1,4-dioxane, anisole was added to obtain a mixed solution, the mixed solution was added to a reaction container, deoxygenated, oil bath polymerized, and after the polymerization reaction was completed, the solution was precipitated and vacuum dried to obtain a modified leveling agent; The method for preparing the antifouling coating comprises the following steps: S1: adding silica to a mixed solution of ethanol and water, ultrasonically treating to obtain a dispersion, heating and stirring, dropping ammonia water and (3-aminopropyl)triethoxysilane, condensing and refluxing, centrifuging, washing the product, and obtaining modified silica; S2: adding modified silica to N,N-dimethylformamide, ultrasonically treating to obtain a modified silica solution, then adding styrene-maleic anhydride copolymer to N,N-dimethylformamide to obtain a copolymer solution, slowly dropping the modified silica solution into the copolymer solution, controlling the dropping temperature, and after the dropping is completed, condensing and refluxing, centrifuging, washing, and drying to obtain a copolymer composite silica; S3: Add the copolymer composite silica and isophorone diisocyanate to tetrahydrofuran, heat to react, and obtain a prepolymer; then add 4,4'-dihydroxydiphenyl disulfide to the prepolymer, continue to heat to react, and after the reaction is completed, add diacetyl oxime, heat to react, and after the reaction is completed, cool to obtain an antifouling coating.

2. The method for preparing the super antifouling light-sensitive glaze according to claim 1, characterized in that: In the step (1), the dosage ratio of feldspar, quartz, calcite and distilled water is (12-18) kg: (4-9) kg: (1-3) kg: (5-10) L. During the ball milling mixing process: the ball milling speed is 200-300 rpm, the ball milling time is 8-12 hours, the mass ratio of glaze slurry, hardener, cross-linking agent, modified leveling agent and silane coupling agent is (5-9): (0.12-0.18): (0.08-0.15): (0.05-0.19): (0.13-0.17), and the stirring mixing time is 4-8 hours.

3. The method for preparing the super antifouling light-sensitive glaze according to claim 1, characterized in that: In the Q1, the molar ratio of maleic anhydride to p-aminophenol is (1-2): (0.9-1.9), the low temperature reaction temperature is 0-1°C, the low temperature reaction time is 3-5h, the vacuum drying temperature is 60-80°C, the vacuum drying time is 10-12h, and the amount ratio of compound 1, p-toluenesulfonic acid, toluene and N,N-dimethylformamide is (8.6-11.2) g: (0.9-1.2) g: (50-65) mL : (10-13) mL, the heating reflux reaction temperature is 110-120°C, and the reaction time is 8-10h; in Q2, the molar ratio of aniline, polyformaldehyde and compound 2 is (1-2): (2-4.2): (1-1.9), the stirring time is 30-45min, the reflux reaction temperature is 120-130°C, the reaction time is 6-8h, and after washing with 5wt% sodium bicarbonate solution, it is washed with deionized water.

4. The method for preparing the super antifouling light-sensitive glaze according to claim 1, characterized in that: In Q3, the molar ratio of compound 3, 4-cyano-4-(thiobenzoyl)valeric acid, poly(ethylene glycol) methacrylate and azobisisobutyronitrile is (2-3):(0.1-0.15):(8-12):(0.02-0.03), the oil bath polymerization temperature is 70-90°C, the polymerization time is 14-16h, and the vacuum drying time is 20-24h.

5. The method for preparing the super antifouling light-sensitive glaze according to claim 1, characterized in that: In the S1, the amount ratio of silicon dioxide, ethanol, water, ammonia water and (3-aminopropyl)triethoxysilane is (2-4) g: (175-350) mL: (25-50) mL: (5-10) mL: (1-2) mL, the ultrasonic treatment time is 10-20 min, the heating temperature is 70-80° C., the rotation speed is 500-700 rpm, the stirring time is 30-45 min, the condensation reflux time is 8-10 h, and the product is washed with ethanol 3-5 times.

6. The method for preparing the super antifouling light-sensitive glaze according to claim 1, characterized in that: In the S2, the mass ratio of modified silica and styrene-maleic anhydride copolymer is (2-4): (1-2), the dropping temperature is 80-90°C, the condensation reflux time is 10-12h, first washed with N,N-dimethylformamide, then washed with ethanol, the drying temperature is 60-80°C, and the time is 10-12h.

7. The method for preparing the super antifouling light-sensitive glaze according to claim 1, characterized in that: In the S3, the molar ratio of the copolymer composite silica, isophorone diisocyanate, 4,4'-dihydroxydiphenyl disulfide and dimethylglyoxime is (4-8): (5.2-10): (0.6-1.1): (0.6-1.2), the heating reaction temperature after adding tetrahydrofuran is 40-50°C, the time is 3-5h, the heating reaction temperature is continued to be 40-50°C, the time is 3-4h, and the heating reaction temperature after adding dimethylglyoxime is 60-70°C, the time is 2-3h.

Citation Information

Patent Citations

  • Stain-resistant glazed tile and production process thereof

    CN112456967A

  • Preparation method of light-cured water-based super-abrasion-resistant highlight wood floor paint

    CN105647260A

  • Antifouling wear-resistant coating for surface protection of inorganic artificial stone as well as preparation and use methods of antifouling wear-resistant coating

    CN115678325A